Abscessed Uterine and Extrauterine Adenomyomas with Uterus-Like Features in a 56-Year-Old Woman - Asiye Safak Bulut; Tevfik Uğur Sipahi (Hindawi Limited, 2013)
Adenomyosis, also known as endometriosis interna, is the presence of endometrial glands and stroma within the myometrium. Its localised form is called adenomyoma and mimics a leiomyoma. Rarely, adenomyomas are located outside the uterus and some of them form uterus-like masses with a thick muscle wall and an endometrium-lined central cavity. They are generally located in the ovary or broad ligament, and, although they are closely related to endometriosis, their pathogenetic mechanisms are different from each other. Müllerian duct fusion defect and subcoelomic mesenchyme transformation theory are two possible pathogenetic mechanisms for this rare entity. Here we report abscessed uterine and extrauterine adenomyomas forming uterus-like masses in the left and right broad ligament and an ectopic adrenal tissue in the left paraovarian region in a 56-year-old woman. Although there is a reported abscessed adenomyosis in the literature, this is the first abscessed extrauterine uterus-like masses with synchronous pelvic pathologies like endometriosis, leiomyomas, adenomyosis, an endometrial polyp, an endocervical polyp, and an ectopic adrenal tissue. This benign lesion gives the impression of leiomyoma, a uterine malformation, or even malignancy preoperatively. Frozen section helps in differential diagnosis.